Acute eye irritation study of a mixture of glyphosate isopropylamine salt and 2,4 D-isopropylamine (Medical Journal of Indonesia, 2003)
This is an acute irritation study of the eye of a mixture of herbicides containing 240 g/l of glyphosate isopropylamine and 2,4 D-isopropylamine in the rabbits. This study was conducted according the methods as dercribed by the United States Environmental Protection Agency (EPA). Our results show that the combination of the herbicides causes mild conjunctivitis, mild chemosis, eye discharge and corneal injury. The ocular alteration, however, was reversible in nature. (Med J Indones 2003; 12: 135-41)